INTERRELATIONSHIP BETWEEN WORK MOTIVATION AND EDUCATIONAL QUALITY MANAGEMENT SYSTEM (Conferencea, 2023)
The work of employees in higher educational institutions is one of the types of work, not only the main element of higher education, but also a necessary component of social work directly related to the entire mechanism of social reproduction.